Susceptibility to adverse drug reactions. Issue 10 (17th July 2019) - Ferner, Robin; Aronson, Jeffrey
Abstract : The pharmacological effects of a drug depend on its concentration at the site of action, and therefore on the concentration in blood and on the dose. The relationship between the concentration or dose and the corresponding effect can usually be represented mathematically as a rectangular hyperbola; when effect is plotted against log concentration or log dose, the curve is sigmoidal. Inevitably, the effect size and the doses causing benefit and harm will differ among individuals, since they are biological phenomena: some individuals are more likely than others to suffer harm at any given dose. Some harmful effects can occur at much lower doses than those used in therapeutics; that is, the log dose–response curve for harm lies far to the left of the log dose–response curve for benefit. Those who suffer such reactions are hypersusceptible . When the dose–response curves for harm and therapeutic effect are in the same range, dose cannot separate the harmful effects from the therapeutic effects, and adverse reactions are collateral . Toxic effects occur when harmful doses are above the doses needed for benefit. In this review we consider factors that influence a subject's susceptibility to adverse drug reactions. Determinants of susceptibility includeI mmunological, G enetic, demographic (A ge andS ex), P hysiological andE xogenous factors (drug–drug interactions, for example), andD iseases and disorders such as renal failure, giving the mnemonicI GASPED . Some susceptibility factors are discrete (for example, all‐or‐none ) and some are continuous; susceptibility can therefore be discrete or continuous; and the factors can interact to determine a person's overall susceptibility to harm.